RADIATION USE EFFICIENCY OF MAIZE UNDER INFLUENCE OF DIFFERENT LEVELS OF NITROGEN FERTILIZATION AND TWO DIFFERENT SEASONAL CONDITIONS - Mohammed, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study to estimate the Radiation Use Efficiency under effect of three levels of nitrogen (N1 = 80 Kg N ha-1, N2 =120 Kg N ha-1, and N3=160 Kg N ha-1) for a set of maize hybrids include (Gloria, Market, Cruze and Draxma) in two different seasons in spring and fall of 2017 in Qlyasn-Sulaimani. The experiment was conducted using split plot design with three replicates . The results revealed higher intensity of PAR in autumn season than that of spring (15.672 and 10.555)MJm-2d-1 respectively that led to higher RUE in autumn revealing (4.311,3.546, and 4.702)g MJ-1 m-2 under the effect of (N1,N2, and N3) respectively, while the results of the autumn were higher (5.237, 4.681, and 6.019) g MJ-1 m-2 under the same levels of nitrogen fertilization, the highest application of nitrogen was more effective in autumn. The RGR and the rate of total dry matter accumulation were higher in autumn season displaying positive performance of studied maize hybrids to the higher intercepted of solar energy as well higher temperature.